2022
DOI: 10.1039/d2na00167e
|View full text |Cite
|
Sign up to set email alerts
|

Morin encapsulated chitosan nanoparticles (MCNPs) ameliorate arsenic induced liver damage through improvement of the antioxidant system and prevention of apoptosis and inflammation in mice

Abstract: Chronic exposure to arsenic over a period of time induces toxicity, primarily in liver but gradually in all systems of the body. Morin hydrate (MH; 2′,3,4′,5,7-pentahydroxyflavone), a potent flavonoid abundantly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…In the group of animals treated with HEMAFER (T6), the improvement was somewhat unnoticeable, as follows: AST, ALT, and ALP, where the values were at 40.6, 51.6, and 70.3 (IU/L), respectively. This research supported the findings of Yaping et al (2018) and [21] Yaping et al, who found that the concentration of silver iron (Ag-Fe3O4) in the liver and kidney was considerably lower than that in the group of Ag-APs. The effects of treatment with this drug revealed a notable improvement in liver enzymes without causing any liver damage., unlike Ag-APs, which caused significant damage to the liver and kidneys.…”
Section: Effect Of Oral Dosage Of Fe 3 O 4 and Chitosan Nanoparticles...supporting
confidence: 92%
“…In the group of animals treated with HEMAFER (T6), the improvement was somewhat unnoticeable, as follows: AST, ALT, and ALP, where the values were at 40.6, 51.6, and 70.3 (IU/L), respectively. This research supported the findings of Yaping et al (2018) and [21] Yaping et al, who found that the concentration of silver iron (Ag-Fe3O4) in the liver and kidney was considerably lower than that in the group of Ag-APs. The effects of treatment with this drug revealed a notable improvement in liver enzymes without causing any liver damage., unlike Ag-APs, which caused significant damage to the liver and kidneys.…”
Section: Effect Of Oral Dosage Of Fe 3 O 4 and Chitosan Nanoparticles...supporting
confidence: 92%
“…To determine the encapsulation efficiency (EE) of MR, freshly purified NPs were diluted ten times in DMSO to dissolve all the NP ingredients. The total amount of MR within the NPs was determined by UV–Vis as described previously ( Mondal et al, 2022 ). The UV absorbance of MR was measured at 358 nm (λ max for MR in DMSO), and the concentration of MR present in the NPs was extrapolated from a calibration curve of MR absorbance at 358 nm versus concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Mulberry pigment-loaded chitosan NPs were developed to improve the antioxidant system and prevent apoptosis and inflammation in mice, leading to the inhibition of arsenic-induced liver injury. This research breaks through limitations such as the insolubility of mulberry pigments that are unfavorable for therapeutic applications, making mulberry pigment-loaded chitosan NPs a better hepatoprotective agent against arsenic toxicity compared with free mulberry pigments ( Mondal et al, 2022 ).…”
Section: Chronic Inflammatory Diseases and Nanomaterialsmentioning
confidence: 99%